Eksistensi Bahasa Jawa dalam Menghadapi Pendidikan Karakter Siswa Sekolah Dasar di Era Society 5.0 - Rofi' Setia Bekti; M. Anas Thohir (LPPM STKIP PGRI Bandar Lampung, 2022)
This research was conducted due to the rampant use of Javanese language that is not right among elementary school students. The purpose of this study is to find out the existence of Javanese language towards the character education of students in elementary school era society 5.o as well as the factors that influence it. The research method used is a case study with a qualitative approach. The population is all students and teachers of elementary schools on the island of Java, while the sample includes 2 teachers and 51 high-class students in two elementary schools in Blitar Regency, one favorite school in the lowlands and another school that is less desirable in mountainous areas. Data collection techniques use observation, questionnaires, and interviews. Data analysis techniques use percentages for questionnaires and coding for interview results. Based on the results of research, the existence of Javanese language towards elementary school students in Blitar Regency is still low. Almost all respondents mixed Krama language with Ngoko language, both Ngoko Lugu and Ngoko Alus in speaking with parents, even some of whom still mix it with Indonesian. This affects the character that students have. Factors that affect this condition are the assistance of parents and families, the uptake of other languages from the environment, and the school that pays less attention to the mastery of Javanese language to students.